Gender Discrimination Law in Pakistan with Legal Perspective; A Quantitative Approach Study - Umair Nasir Sethi; Hafiz Abdul Rehman Saleem (Research Journal of Psychology, 2025)
This discussion explores gender discrimination, highlighting its pervasive impact across society and its effects on individuals. A literature review confirms the negative consequences of such discrimination, with legal systems being a focal point. Using a quantitative approach, data on gender bias in court verdicts was analyzed through regression models, which indicated slight but statistically non-significant gender-based patterns. These findings suggest the complex, layered nature of gender discrimination. While some progress is evident, inherent biases persist. Future research is recommended to adopt a dual approach, integrating both quantitative and qualitative methods to better understand these dynamics.